Outcomes of primary membranous nephropathy based on serum anti-phospholipase A2 receptor antibodies and glomerular phospholipase A2 receptor antigen status: a retrospective cohort study. Issue 1 (1st January 2020) - Yin, Peihong; Wang, Junxian; Liang, Wenyi; Zhan, Linda; Liu, Yuanhao; Lin, Jian; Chen, Xiaohong; He, Yingqin; Jian, Hongyun; Xie, Zhibin; Tan, Xiaofan; Ye, Qing; et al.
Abstract: Introduction: Primary membranous nephropathy (PMN) is associated with the anti-phospholipase A2 receptor (anti-PLA2R) antibody in 70% of cases. Some anti-PLA2R-negative patients have the PLA2R antigen in renal tissue. This study examined the prognosis of patients with PMN according to their serum anti-PLA2R antibody (SAb) and glomerular PLA2R antigen (GAg) status. Methods: Patients diagnosed with PMN were included retrospectively. Patients were grouped according to their PLA2R status into the SAb−/GAg−, SAb−/GAg+, and SAb+/GAg + groups. Baseline data, renal biopsy results, treatment, and clinical data were compared among the groups. Cox univariable and multivariable analyses examined the factors related to complete remission (CR). Results: A total of 114 patients were enrolled; 10 (9%) in the SAb−/GAg−, 23 (20%) in the SAb−/GAg+, and 81 (71%) in the SAb+/GAg+ groups. Cumulative CR rate showed a significant difference between the SAb−/GAg − and SAb+/GAg+ groups (log-rank p = 0.003). The multivariable Cox proportional hazard analysis showed that age (HR = 0.968; 95%CI = 0.946–0.990; p = 0.005), SAb+/GAg+ versus SAb−/GAg− (HR = 0.387; 95%CI = 0.190–0.788; p = 0.009), SAb−/GAg+ versus SAb−/GAg− (HR = 0.398; 95%CI = 0.169, 0.939; p = 0.035), total renal chronicity score ≥2 (HR = 0.461, 95%CI: 0.277–0.766, p = 0.003), and IgA deposition (HR = 2.596; 95%CI = 1.227–5.492; p = 0.013) were all independently related ( p < 0.05) to CR. Conclusions: The SAb and GAg status was an indicator of PMN prognosis. The patients with SAb−/GAg − had an increased likelihood of achieving CR than those with SAb−/GAg+ and SAb+/GAg+.